A Straightforward, Purification-Free Procedure for the Synthesis of Ando and Still–Gennari Type Phosphonates - Janicki, Ignacy; Kiełbasiński, Piotr (Synthesis, 2021)
Z-Selective Still–Gennari and Ando modifications of the typically E-selective Horner–Wadsworth–Emmons reaction are highly valuable synthetic tools in organic chemistry. These procedures are based on application of bis(2,2,2-trifluoroethyl) phosphonates or diaryl phosphonates, respectively, for the olefination of carbonyl groups. In our research, we present an improved, straightforward, purification-free procedure for the synthesis of these reagents. The key step of our procedure is the reaction of phosphonic dichlorides with the appropriate sodium alkoxides, which results in 52–97% isolated yields of the desired products on a gram scale. The whole three-step process is performed in one pot. Most importantly, the product is obtained in over 95% purity after simple extraction, avoiding column chromatography and distillation. Moreover, we present the synthesis of a novel Still–Gennari type reagent, bis(1,1,1,3,3,3-hexafluoroisopropyl) phosphonates, which may exhibit improved Z-selectivity in Still–Gennari olefinations.
Keywords: Horner–Wadsworth–Emmons (HWE) reaction; Still–Gennari olefination; Ando olefination; stereoselective synthesis; Wittig reaction; phosphonates; alkenes; C=C bond formation